Educational Management of Character Values Based on Ta’limul Muta’allim: Strengthening Ethical Practices among Santri - mahmudi; Sunarto; Siti Roudhotul Jannah (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of character education values based on Ta’limul Muta’allim and their role in shaping the ethical behavior of santri, with a focus on the learning process, influencing factors, and educational management practices. A qualitative field research approach was employed, with data collected through observation, indepth interviews, and documentation involving teachers, administrators, and students. Data analysis was conducted using data reduction, data display, and conclusion drawing through an inductive approach, while validity was ensured through source and technique triangulation. The findings reveal that the learning process is carried out through traditional methods such as bandongan and sorogan, combined with direct character value internalization. The implemented values include sincerity, humility (tawadhu’), discipline, patience, and respect for teachers, which are reflected in students’ daily behavior. These values contribute to the development of ethical attitudes such as respect, responsibility, and obedience to institutional rules. Supporting factors include a religious environment, teacher role modeling, and structured habituation, while inhibiting factors involve differences in student backgrounds and levels of awareness. The study implies that effective educational management, particularly in planning, supervision, and character-based learning strategies, is essential to strengthen the internalization of ethical values and ensure sustainable character development.